Digital Transformation and Its Role in Improving Democracy: A Systematic Literature Review - Poiran; Syah Amin Albadry; Burhanuddin; Sasmita Rusnaini (Open Access Indonesia Journal of Social Sciences, 2023)
In order to achieve a more inclusive and robust democracy, it is important to understand the role of digital transformation and how technology can be used as a tool to strengthen public participation, ensure transparency and increase government accountability. By looking at real examples and broader implications of digitalization in the context of democracy, existing opportunities and challenges can be identified, and appropriate policies can be formulated for a better democratic future. This review aimed to describe the digital transformation and its role in improving democracy. Literature search efforts are carried out by searching on search engines using certain keywords. Articles that match the inclusion criteria are reviewed in depth. Digitalization has played an important role in strengthening democracy in an unprecedented way. By expanding public participation, increasing transparency, and strengthening government accountability, digital technology has provided new opportunities for citizens to engage in political processes and effect social change. However, keep in mind that challenges and risks associated with digitization also exist, such as the spread of false information and data privacy.